Event Management: The Heart of the Quality Program - Olson, John D.; Harrison, Chantal R. (Seminars in Thrombosis and Hemostasis, 2012)
Learning from mistakes or failures is the purpose of a laboratory's event management system. Laboratories that systematically and effectively learn from failures which occur especially from small mistakes and problems rather than from consequential adverse events, are rare. An effective event management program often requires a cultural sea change that emphasizes a process of detection and reporting of errors that is without reprisal. An approach to development of such an event management program is described in this article. Steps of event management including engagement of the staff, tools used, steps of evaluation, application to all elements of laboratory management, and culture change necessary are discussed.
Keywords: quality; error; failure; Quality System Essentials